Kelembapan Udara Terhadap Kenyamanan Calon Penumpang Kereta Api di Ruang Tunggu Stasiun Lempuyangan - Putri, Famelga Clea (Journal of Academia Perspectives, 2022)
Lempuyangan Station is a place to pick up and drop passengers using rail transportation services, both from within and outside the city of Yogyakarta. In addition to good service, a convenient location is also needed in serving consumers. The problem faced in this research is how to identify and measure and evaluate the physical environment in the waiting room of Lempuyangan Station. The results of this study aim to provide recommendations on how to create a waiting room that is in accordance with the standards of comfort and health levels that suit your needs. The analytical method used is ANOVA (Linear Regression and Multiple Linear Regression). Quantitative data was collected through the distribution of questionnaires to 50 respondents, namely prospective passengers which included questions about air humidity with yes and no answer choices. Based on the results of data acquisition regarding humidity using the descriptive method, it was obtained that the humidity data in the waiting room of the lempuyangan station was 57.5%RH, this value was outside the specified threshold value. These data indicate that the existing humidity level is not in accordance with the national standard/ideal. The room humidity rating is 57.5%RH, which means this room exceeds the humidity threshold value, with the comfort zone standard of only 40 – 50% RH.